OsSIDP366, a DUF1644 gene, positively regulates responses to drought and salt stresses in rice. Issue 5 (25th September 2015) - Guo, Chiming; Luo, Chengke; Guo, Lijia; Li, Min; Guo, Xiaoling; Zhang, Yuxia; Wang, Liangjiang; Chen, Liang
Abstract: Domain of unknown function 1644 (DUF1644) is a highly conserved amino acid sequence motif present only in plants. Analysis of expression data of the family of DUF1644‐containing genes indicated that they may regulate responses to abiotic stress in rice. Here we present our discovery of the role of OsSIDP366, a member of the DUF1644 gene family, in response to drought and salinity stresses in rice. Transgenic rice plants overexpressing OsSIDP366 showed enhanced drought and salinity tolerance and reduced water loss as compared to that in the control, whereas plants with downregulated OsSIDP366 expression levels using RNA interference (RNAi) were more sensitive to salinity and drought treatments. The sensitivity to abscisic acid (ABA) treatment was not changed in OsSIDP366 ‐overexpressing plants, and OsSIDP366 expression was not affected in ABA‐deficient mutants. Subcellular localization analysis revealed that OsSIDP366 is presented in the cytoplasmic foci that colocalized with protein markers for both processing bodies (PBs) and stress granules (SGs) in rice protoplasts. Digital gene expression (DGE) profile analysis indicated that stress‐related genes such as SNAC1, OsHAK5 and PRs were upregulated in OsSIDP366 ‐overexpressing plants. These results suggest that OsSIDP366 may function as a regulator of the PBs/SGs and positively regulate salt and drought resistance in rice. Abstract : OsSIDP366 is a member of DUF1644 family in rice which co‐localizes with processing bodies and stress granules. Over‐expression of OsSIDP366 enhances drought and salt tolerance, reduces water loss rate and up‐regulates stress‐related genes in rice, suggesting the positive role of OsSIDP366 in abiotic stress response.